Effect of Astaxanthin on Immune Function and Myocardial Injury in Mice with Chronic Sleep Deprivation - FENG Biyun, LI Lingyan, LI Ming, ZHANG Jiayuan, QI Huanyang, CHEN Pingping, XU Guanghui (Shipin Kexue)
Objective: To explore the effect of astaxanthin on immune function and myocardial injury in mice with chronic sleep deprivation (CSD). Methods: A modified multi-platform water environment method was used to establish an CSD mouse model for two weeks. At the same time, mice were intragastrically administered with astaxanthin at different doses. Immune function and myocardial injury were evaluated by measuring organ coefficients as well as using the carbon clearance test and commercial enzyme-linked immunosorbent assay (ELISA) kits. The targets of astaxanthin and related biological processes and pathways were analyzed by network pharmacology. Results: Compared with the model group, body mass, phagocytic index and clearance index significantly increased in the treatment groups, and heart, spleen and pancreas coefficients decreased. Moreover, the levels of serum creatine kinase (CK), superoxide dismutase (SOD), tumor necrosis factor-α (TNF-α), glutathione peroxidase (GSH-Px), interleukin (IL)-1β, IL-6, nitric oxide synthase (NOS) and γ-glutamyl transpeptidase (γ-GT) rose markedly in each treatment group, and the level of malondialdehyde (MDA) significantly declined. Conclusion: Astaxanthin greatly ameliorates immune dysfunction and myocardial injury caused by CSD, perhaps by regulating the neurotrophic factors, Toll-like receptor, nuclear factor-κB (NF-κB), T cell receptor and apoptosis signaling pathways and inhibiting inflammatory response.